PREVALENCE AND FACTORS ASSOCIATED WITH MATERNAL POSTPARTUM HAEMORRHAGE IN KHYBER AGENCY, PAKISTAN - Gani, Gani N; Ali, Ali TS (Journal of Ayub Medical College Abbottabad, 2013)
Background: Postpartum haemorrhage (PPH) is one of the main causes of maternal mortality globally. The objective of this study was to estimate the prevalence of PPH and identify factors associated with PPH in Khyber Agency, Pakistan. Methodology: A quantitative, cross-sectional study design was selected to estimate the prevalence and associated factors for PPH among married women aged 15-49 years, residing in the Khyber Agency, FATA, Pakistan. A pre-tested structured questionnaire was adapted with some modifications to interview 1,000 women. Results: Prevalence of PPH was 21.3% in the study population. Factors associated with PPH were age, number of pregnancies, duration of labour, avoidance of milk, insertion of homemade remedies in vagina, retained placenta, and rest during postpartum period. Conclusion: Poor infrastructure, lack of appropriate training for healthcare providers, economic conditions, and negative cultural practices are some amongst the multiple factors that have a perilous impact on women’s health, particularly women of reproductive age. The morbidities were the result of malpractices ingrained in the community. Keywords: Postpartum Haemorrhage, Maternal Mortality, Morbidity, Postpartum, Malpractices